Workforce Characteristics of Early Career Neonatologists and Comparison of Practice Sites - Nestander, Matt; Day, Colby; Lucke, Ashley; Gautam, Shiva; Horowitz, Eric; Bernstein, Sarah M.; Bhatia, Anisha (American Journal of Perinatology, 2023)
Objective Transitioning into the early career physician workforce is a uniquely challenging period in a neonatologist's career. There are limited educational opportunities in fellowship regarding career progression, practice models, and benefits. Understanding these factors are key when searching for employment. This study evaluates the early career neonatologist (ECN) workforce and employment characteristics to improve identification of professional needs.Study Design An anonymous 59-question cross-sectional survey was distributed in July 2020 to members of the American Academy of Pediatrics Section on Neonatal Perinatal Medicine Trainees and Early Career Neonatologists (TECaN). The survey instrument was designed using SurveyMonkey and assessed search methods for identifying employers, employment contract details, and professional duties. Questions addressed clinical service time, level of acuity, protected research time, financial compensation, benefits, job search methods, and promotion requirements. Comparisons were drawn between respondents exclusively working in a university-based setting and respondents employed in nonuniversity locations. Responses were collected using SurveyMonkey and then extracted to a Microsoft Excel Workbook for analysis. Statistical analysis was performed using SAS version 9.4.Results Of 1,302 eligible members, 348 people responded (26.7%). Forty-six percent of respondents worked in a university setting and 54% worked in a nonuniversity setting. Using employment site as a discriminator, significant differences were noted in scheduling models. University-located respondents were more likely to work 2-week block schedules, fewer weekend/weeknight call, less clinical weeks per year, and more research/administrative weeks per year. Between university and nonuniversity located positions, benefits were largely comparable, while factors perceived as influential toward promotion varied depending on practice site.Conclusion This study provides ECNs with a contemporary workforce description vital to graduating TECaN seeking employment or renegotiating professional obligations. While benefits were largely similar based on practice site, promotion factors and scheduling models may vary depending on location.Key Points
Keywords: neonatologist; workforce; early career; practice location; neonatal–perinatal fellowship; contract negotiation